2005
DOI: 10.1111/j.1440-1681.2005.04173.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of hydrocortisone on plasma nitrate/nitrite activity and forearm vasodilator responsiveness in normal human subjects

Abstract: 1. The aim of the present study was to examine the acute effects of cortisol infusion on plasma nitrate/nitrite (NO) activity and forearm vascular responsiveness to acetylcholine. 2. We performed two randomized, placebo-controlled, cross-over studies. Study A examined the effects of intravenous hydrocortisone (200 mg over a 3 h period) on blood pressure (BP) and plasma NO activity in six healthy male volunteers. Study B examined the effects of intra-arterial hydrocortisone on cholinergic vasodilator responsive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Additionally, it has been reported that cortisol impairs NO production measured by NOx − levels attributing thus, the cortisol-induced hypertension to the NO deficiency in both human and experimental model [53] , [54] . However, most of the studies have examined the interaction between cortisol and arterial hypertension in male subjects [55] and no one examined the effects of exercise training on endocrine-inflammatory mediators in hypertensive postmenopausal women. In our study, we found no effects of the exercise training in the cortisol concentration in hypertensive postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been reported that cortisol impairs NO production measured by NOx − levels attributing thus, the cortisol-induced hypertension to the NO deficiency in both human and experimental model [53] , [54] . However, most of the studies have examined the interaction between cortisol and arterial hypertension in male subjects [55] and no one examined the effects of exercise training on endocrine-inflammatory mediators in hypertensive postmenopausal women. In our study, we found no effects of the exercise training in the cortisol concentration in hypertensive postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains unclear which of these mechanisms are causal rather than epiphenomena or amplifiers and modulators of the sympathetic system. Current interest is focused on vascular effects of cortisol and the role of the nitric oxide (NO) system (Whitworth et al, 2000;Williamson et al, 2005), which transmits biological information in both the central nervous and the cardiovascular system under physiological and pathophysiological conditions (Moncada, 1992). There is evidence that isosorbide dinitrate (ISDN) given to rats undergoing withdrawal worsens withdrawal signs, suggesting NO to be involved in AWS (Adams et al, 1995) and to modulate cardiovascular effects (Kahkonen and Zvartau, 2003).…”
Section: Discussionmentioning
confidence: 99%